NANOSTRUCTURED CARBON MATERIALS IN EMISSION ELECTRONICS - А. F. Belyanin; V. V. Borisov; A. S. Bagdasaryan (Российский технологический журнал, 2017)
This paper considers the influence of formation conditions on the composition and structure of polycluster diamond films, diamond-like carbon films and carbon nanowalls. Polycluster diamond films were obtained from a gas mixture of hydrogen and methane activated with arc and microwave discharges as well as by applying heat (i.e. hot-wire method). Diamond-like carbon films were obtained by using the methods of high-frequency magnetron sputtering, high-frequency diode discharge in a gas mixture of cyclohexane and hydrogen, graphite ion-beam sputtering. Carbon nanowalls were obtained from a gas mixture of hydrogen and methane activated with a direct current glow discharge. The composition and structure of synthesized carbon materials are explored by using the methods of electron and atomic force microscopy, X-ray diffractometry and Raman spectroscopy. Finally, the authors also study the interconnection between the composition and structure of synthesized carbon materials and electric and functional characteristics of cold cathodes based on them.